Osthole exhibits an antitumor effect in retinoblastoma through inhibiting the PI3K/AKT/mTOR pathway via regulating the hsa_circ_0007534/miR-214-3p axis - Xiufang Lv; Haojiang Yang; Hui Zhong; Li He; Li Wang (Pharmaceutical Biology, 2022)
Context Osthole shows antitumor effects in various tumours. Studies describing the effect of osthole on retinoblastoma (RB) are rare. Objective This study investigates the antitumor activity of osthole on RB. Materials and methods RB cells were treated with different concentrations of osthole and then subjected to cell viability, colony formation, apoptosis, and western blot assays. The expression of hsa_circ_0007534 in RB tissues was determined by qRT-PCR. Hsa_circ_0007534 overexpression plasmid (oe-circ_0007534), miR-214-3p mimics and negative controls were transfected into RB cells to investigate cell viability. Athymic nude mice were injected with Y-79 cells to establish subcutaneous RB models. These mice were treated with osthole (0.5 mmol/kg) or corn oil for 36 days. Tumour tissues were collected for further analysis. Results Osthole inhibited cell viability of RB cells with an IC50 of 200 μM for 24 h treatment and 120 μM for 48 h treatment, respectively. Hsa_circ_0007534 was increased significantly in RB tissues as compared to the matched nontumor tissues (p < 0.001). Oe-circ_0007534 counteracted the inhibitory effect of osthole on cell viability and colony numbers of Y-79 cells (p < 0.01). In vivo experiments indicated osthole significantly decreased the expression of hsa_circ_0007534 (p < 0.01) and increased the level of miR-214-3p in vivo. Furthermore, as compared to the control, osthole decreased the ratios of p-PI3K/PI3K, p-AKT/AKT and p-mTOR/mTOR (p < 0.01). However, hsa_circ_0007534 overexpression reversed the effect of osthole on the PI3K/AKT/mTOR pathway. Discussion and conclusions Osthole exhibited an antitumour effect in RB, providing a scientific basis for further research and clinical applications of osthole in RB treatment.